2018
DOI: 10.12720/sgce.8.1.38-47
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of waste polyethylene pyrolysis oil as partial substitute for diesel fuel in a DI diesel engine

Abstract: This study aims to utilize pyrolysis oil produced from the pyrolysis of waste polyethylene in a direct injection (DI) diesel engine. In this paper, the performance and emission of a diesel engine have been studied using blends of waste polyethylene pyrolysis oil with diesel fuel under different loads condition. The waste polyethylene pyrolysis oil (WPO) used in this work was produced from the sequential pyrolysis and catalytic reforming of polyethylene bag after crushing and washing using natural zeolite (NZ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In another study, the performance of catalytically reformed PE derived pyrolysis oil with natural zeolite (NZ) catalyst was analyzed in a fourcylinder and four-stroke diesel engine. 303 In this case, diesel blended pyrolysis oil showed higher BTEs with lower BSFC. Furthermore, NO x emission was lower but CO, hydrocarbon and smoke emissions were higher compared to commercial diesel at higher loads.…”
Section: Applications Of Pyrolysis Productsmentioning
confidence: 76%
See 1 more Smart Citation
“…In another study, the performance of catalytically reformed PE derived pyrolysis oil with natural zeolite (NZ) catalyst was analyzed in a fourcylinder and four-stroke diesel engine. 303 In this case, diesel blended pyrolysis oil showed higher BTEs with lower BSFC. Furthermore, NO x emission was lower but CO, hydrocarbon and smoke emissions were higher compared to commercial diesel at higher loads.…”
Section: Applications Of Pyrolysis Productsmentioning
confidence: 76%
“…Interestingly, 20% blends of pyrolysis oil matched with European diesel fuel standards (EN590). In another study, the performance of catalytically reformed PE derived pyrolysis oil with natural zeolite (NZ) catalyst was analyzed in a four-cylinder and four-stroke diesel engine . In this case, diesel blended pyrolysis oil showed higher BTEs with lower BSFC.…”
Section: Applications Of Pyrolysis Productsmentioning
confidence: 99%
“…It is also evident from the properties of plastic fuel, which are responsible for poor combustion inside the cylinder. The hydrocarbon emission can be reduced by improving the properties of plastic oil with higher oxygen content fuel, so that the hydrocarbon emission coming in the exhaust can undergo combustion inside the cylinder [6,7]. The HC emissions are minimum for diesel and for blend HC emission increases by 17% for P20.…”
Section: Emission Characteristicsmentioning
confidence: 99%
“…The plastic oil blends can be considered as alternative fuel for diesel engines with acceptable performance addressing the environmental concerns as well [6]. The experimental outcomes indicated that the performance with plastic oil blends were comparable to diesel operation while the fuel consumption decreased marginally with WPO and diesel fuel blends [7]. The process of obtaining fuel from the plastics is an important source of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Viswanath et al [25] also concluded that brake thermal efficiency of blends are lower compared to diesel, but 25% blending shows similar performance to that of diesel. Syamsiro et.al [26] also found that brake thermal efficiencies of waste polyethylene oil (WPO) are quite higher as compared to that of diesel. However, the difference was not significant since the calorific value of WPO which is found to be similar than that Some studies above have shown that the pyrolysis of plastic wastes become oil product was conducted a good result.…”
Section: Introductionmentioning
confidence: 99%